Research Methods in a Multinational Business Environment and Implications for Capital Formation: Application of Cross-Sectional Autoregressive Distributed Lag Methods - Halwan, Musaad M.; Bin, Zhang Y.; Ameer, Waqar; Mumtaz, Nosheen; Mumtaz, Ayesha; Amin, Azka (Frontiers in Psychology, 2022)
We explore whether Foreign Direct Investment outflows augments or obstruct public or private capital in developing countries by decomposing domestic capital into private and public capital. While developed countries are the primary source of foreign direct investment outflows (OFDI), developing economies have become the primary source of OFDI over the past 30 years. We apply cross-sectional autoregressive distributed lags (CS-ARDL) methods to overcome the issue of endogeneity and cross-sectional dependency in our dataset. This study analyses the interaction effects of foreign direct investment and institutional quality in promoting aggregate domestic capital formation in developing countries. Our empirical results show that FDI outflows augment private capital formation and additionally, institutional quality (IQ) also upsurge private capital formation. Conversely, as per results, FDI outflows obstruct public capital formation, and IQ crowds out public capital formation significantly while private capital crowds out FDI inflows. As per result estimations, we notice that OFDI crowds in private capital formation, thus; we conclude that the private sector controls majority of the sectors for developing countries and role of public sector is quite minimal. We conclude that private and public capital possess different attributes; thus, clubbing them together might result in aggregation bias Our result estimations provide several useful policy implications.